2017
DOI: 10.1002/jts.22245
|View full text |Cite
|
Sign up to set email alerts
|

Response to Cognitive Processing Therapy in Veterans With and Without Obstructive Sleep Apnea

Abstract: Recent studies have called attention to the need for enhancing treatment outcome in trauma-focused psychotherapies, such as cognitive processing therapy (CPT), with veterans. Given the prevalence of posttraumatic-related sleep disturbances, and the role of sleep in emotional learning and processing, sleep quality may be a target for improving CPT outcome. Elevated rates of obstructive sleep apnea (OSA) have been reported in samples of veterans with posttraumatic stress disorder (PTSD); however, the impact of O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Uncontrolled SDB may attenuate the effect of some therapeutic intervention in this domain, 39 but the study by Sweetman et al 40 shows that treatment for insomnia can be effective in the presence of comorbid sleep apnea. This situation is further complicated by the fact that low CPAP adherence rates are repeatedly observed among patients with PTSD, 41,42 and few evidence-based interventions exist for promoting CPAP adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Uncontrolled SDB may attenuate the effect of some therapeutic intervention in this domain, 39 but the study by Sweetman et al 40 shows that treatment for insomnia can be effective in the presence of comorbid sleep apnea. This situation is further complicated by the fact that low CPAP adherence rates are repeatedly observed among patients with PTSD, 41,42 and few evidence-based interventions exist for promoting CPAP adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that examined whether baseline OSA affected change in PTSD symptoms over the course of psychotherapy were more consistent. A retrospective study of Veterans who had completed CPT at a VA found that those with OSA ( n = 69) showed less symptom improvement than those without OSA ( n = 276) [99••]. However, those with OSA who were being treated with CPAP showed more improvement than those who were not engaging in OSA treatment.…”
Section: Non-pharmacological Treatment Of Sleep Disordersmentioning
confidence: 99%
“…It appears that evaluating and treating independent (i.e., comorbid) sleep disorders in PTSD patients is an emerging paradigm with clear-cut opportunities to improve health outcomes in these vulnerable patients [33, 7678]. However, many questions and some controversies are developing in both the research and clinical realms.…”
Section: Discussionmentioning
confidence: 99%